1997
DOI: 10.1007/s001250050852
|View full text |Cite
|
Sign up to set email alerts
|

CD95 and CD95-ligand expression in endocrine pancreas of NOD, NOR and BALB/c mice

Abstract: The non-obese diabetic (NOD) mouse is widely used to study the pathogenesis of insulin-dependent diabetes mellitus. However, the mechanisms responsible for beta-cell destruction, in this model, are still poorly defined. The CD95/CD95L system among other effector systems has been implicated in beta-cell death. In this study we investigated in NOD, non- obese resistant (NOR) and Balb/c mice the expression of CD95 and CD95L in alpha and beta pancreatic cells by immunohistochemistry and immunofluorescence. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 9 publications
4
16
0
Order By: Relevance
“…Fas was not detected in rat islet ␤ cells during the postnatal period or in young adult mice, including NOD, in agreement with our data (Hanke, 2000;Signore et al, 1997;Thomas et al, 1999). Neurons and Schwann cells can express both Fas and FasL, and this coexpression is thought Immunohistochemistry for Bcl-2 in control and NODscid pancreata during the early postnatal period.…”
Section: Innervation In Neonatal Mousesupporting
confidence: 93%
See 1 more Smart Citation
“…Fas was not detected in rat islet ␤ cells during the postnatal period or in young adult mice, including NOD, in agreement with our data (Hanke, 2000;Signore et al, 1997;Thomas et al, 1999). Neurons and Schwann cells can express both Fas and FasL, and this coexpression is thought Immunohistochemistry for Bcl-2 in control and NODscid pancreata during the early postnatal period.…”
Section: Innervation In Neonatal Mousesupporting
confidence: 93%
“…In rat islets, FasL was detected during the first 3 days of life and disappeared thereafter (Hanke, 2000). In young adult control and NOD mice, FasL was not observed in islet ␤ cells (Thomas et al, 1999) but was observed in surrounding ␣ cells (Signore et al, 1997). Our observations confirm the absence of FasL expression in mouse ␤ cells under normal conditions.…”
Section: Innervation In Neonatal Mousesupporting
confidence: 79%
“…According to our experiments (Fig. 2 and data not shown) and the experience of others (38,42,43), murine -cells express FasL neither spontaneously nor after exposure to pro-inflammatory cytokines, excluding the possibility of suicide/fratricide triggered by Fas:FasL interactions. However, these results are contrasted by a recent report by SuarezPinzon et al (44), which found FasL expression on a minority of R2D6 + islet cells of NOD mice.…”
Section: Discussionsupporting
confidence: 54%
“…The fact that diabetogenic CD4 + T cells spare α cells and other endocrine islet cells cannot be taken as an argument against a role for Fas in β-cell lysis by CD4 + T cells; these other islet cells may be resistant to Fas-mediated cell death. In fact, IL-1 has been shown to selectively induce Fas expression on β cells but not on other endocrine cells (26,27), and α cells express FasL, but not Fas (47).…”
mentioning
confidence: 99%